Modern consumption pattern of social networking sites and its impact on the mental health of adolescents - Labidi, Amal; Amara, Boudjemaa; Djahnit, Hamza (International journal of health sciences, 2024)
Social Media is taking part in different types of online networking, so they are integral in the lives of adolescents. Practitioners need to be able to assess risk, The onset of mental health problems peaks between adolescence and youth and social media are potentially a new dimension to consider. Adolescent voices and practitioner perspectives are central to understanding the relationship between social media and mental health of adolescents. they are rapidly shifting into social media use which has impact at both ends, as boon in form of communication and as bane in the form of mental health problems.